2010
DOI: 10.1158/0008-5472.sabcs10-pd10-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD10-02: Round-Robin Review of HER2 Testing in the Context of Adjuvant Therapy for Breast Cancer (NCCTG N9831/BCIRG006/BCIRG005)

Abstract: Identification of HER2 as an important cellular marker in the biology and treatment of breast cancer has highlighted the importance of reliable testing methodology. Controversy exists regarding type of test, reliability, definition of positivity, and which test may best predict for patient (pt) efficacy to anti-HER2 therapies. Purpose: To determine the concordance between HER2 results by 3 central laboratories, impact of round-robin adjudication of discordant cases, and heterogeneity in HER2 results using spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…otherwise met criteria for trial N9831. However, in a separate article describing a HER2 testing round robin study, Dr Perez et al ( 6 ) reported that, despite excellent concordance, the overall discordance for IHC and FISH testing among international experts were 4% and 3%, respectively, which exceeds the 1% reported in the current analysis ( 1 ). Those data highlight persistent issues of assay interpretation, tumor heterogeneity, and platform robustness, even among experts in the fi eld, which continue to challenge HER2 testing in daily practice.…”
contrasting
confidence: 62%
“…otherwise met criteria for trial N9831. However, in a separate article describing a HER2 testing round robin study, Dr Perez et al ( 6 ) reported that, despite excellent concordance, the overall discordance for IHC and FISH testing among international experts were 4% and 3%, respectively, which exceeds the 1% reported in the current analysis ( 1 ). Those data highlight persistent issues of assay interpretation, tumor heterogeneity, and platform robustness, even among experts in the fi eld, which continue to challenge HER2 testing in daily practice.…”
contrasting
confidence: 62%